PENGARUH EFEKTIVITAS SIA, PEMANFAATAN TI DAN KEMAMPUAN TEKNIS PEMAKAI SIA TERHADAP KINERJA INDIVIDU - Artha Dewi, Ni Luh Ayu; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi, 2017)
Individual performance affects the success of a company, it is expected individual can achieve organizational objectives with the quantity of work, quality of work, timeliness, monitoring supervisor, and the influence of co-workers. The purpose of this study is to determine the effectiveness of accounting information systems, utilization of information technology and technical capabilities users accounting information system of individual performance. This study was conducted on 31 credit cooperatives in Karangasem regency. Samples in this study were 124 respondents to the technical determination of the sample used is purposive sampling. Data collection methods used were a questionnaire method. Data analysis technique used is multiple linear regression. The results of this study found that the effectiveness of accounting information systems, utilization of information technology and technical capabilities users of accounting information system have positively affects the performance of individuals.
Keywords: effectiveness SIA; exploiting IT; technical ability wearer SIA; individual performance